(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes the gender characteristics of the phenomenon of anxiety and the role of family upbringing in its formation based on scientific sources. According to the results of the research, the level of anxiety manifests itself differently in women and men, and detailed information is provided on the fact that, in addition to biological factors, family upbringing styles also have a significant impact on this process.